A study on multiple array method of birdcage coils to improve the signal intensity and homogeneity in small‐animal whole‐body magnetic resonance imaging at 7 T. Issue 1 (29th November 2019) - Heo, Phil; Kim, Han‐Joong; Han, Sang‐Doc; Kim, Donghyuk; Im, Geun Ho; Kim, Soobum; Kim, Kyoung‐Nam
Abstract: Birdcage (BC) coils generate a homogeneous magnetic field (∣ B 1 ∣), whose strength depends on the length of the coils, the number of legs, the resonance frequency, the excitation method, and the length‐to‐diameter ratio. BC coils with a shorter distance between the end rings produce a more intense ∣ B 1 ∣ field with a higher level of homogeneity. Here, we propose a combination of overlapping and nonoverlapping radiofrequency volumetric BC coils for small‐animal magnetic resonance imaging (MRI) working at 7 T with a frequency of 300 MHz to improve the ∣ B 1 ∣‐field homogeneity and intensity along the main magnetic field (∣ B 0 ∣) direction. The first combination consisted of two overlapping BC (o‐BC) coils, in which each coil is half the length of the imaging object. A combination of two nonoverlapping BC coils separated by a small gap (nog‐BC) was also developed. In order to improve the performance of the nog‐BC coil, we attached a decoupling capacitor. In computational calculations, the proposed o‐BC coil configuration showed an increased homogeneity in the ∣ B 1 ∣ field along the ∣ B 0 ∣ direction compared with the other coils. The experimental bench tests of the o‐BC coil configuration showed a high decoupling coefficient between the BC coils, which allowed each of them to be used individually for transmission and reception. The o‐BC coil was able to maintain a high transmission efficiency without signal interference while exhibiting an increased ∣ B 1 ∣‐field homogeneity compared with other coils. In this study, the advantages of the o‐BC coils are demonstrated using electromagnetic simulations and MRI on a homogenous phantom and an in vivo mouse body.